Plot Outlines of 100 Famous Plays - Cartmell, Van H. (New York Barnes and Noble, Inc, 1958)
Plot Outlines of 100 Famous Plays gives complete synopses of 100 important American and European plays. It is a convenient handbook for students and lovers of the drama.
Keywords: Fiction